The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.14712/23362936.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System under Ketamine/xylazine and Pentobarbital Anaesthesia in a Wistar Rat Model: A Chronobiological View

Abstract: Key words: Anaesthesia -Interval -Ketamine/xylazine -Pentobarbital -RatHeart rate variability Abstract:The aim of the present study was to determine the effect of ketamine/ xylazine and pentobarbital anaesthesia on heart rate variability as a marker of autonomic nervous system activity. The experiments were performed in ketamine/ xylazine (10 mg/kg/15 mg/kg) and pentobarbital (40 mg/kg, i.p.) anaesthetized female Wistar rats, after adaptation to a light-dark cycle of 12 hours light: 12 hours dark. Heart rate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…24 Increasing parasympathetic activity and suppressing sympathetic and baroreceptor activity under ketamine/xylazine anesthesia on rats were demonstrated. 25 Therefore decreasing neurogenic activity in zoletil-xylazine anesthetized animals obtained in our experiments might be a result of sympathetic activity suppression. Sedation under inhalational of nitrous oxide shifted the sympathetic-parasympathetic balance toward the parasympathetic dominance via suppression of sympathetic activity.…”
Section: Discussionmentioning
confidence: 59%
“…24 Increasing parasympathetic activity and suppressing sympathetic and baroreceptor activity under ketamine/xylazine anesthesia on rats were demonstrated. 25 Therefore decreasing neurogenic activity in zoletil-xylazine anesthetized animals obtained in our experiments might be a result of sympathetic activity suppression. Sedation under inhalational of nitrous oxide shifted the sympathetic-parasympathetic balance toward the parasympathetic dominance via suppression of sympathetic activity.…”
Section: Discussionmentioning
confidence: 59%
“…Svorc et al 22 corroborated this study: the authors concluded that anaesthesia increased HRV, with increased parasympathetic modulation of the heart determining the effect of ketamine/xylazine with pentobarbital.…”
supporting
confidence: 60%
“…However, the slightest alterations of HR were observed using ketamine and xylazine anesthesia [79]. Ketamine and xylazine were found to increase parasympathetic activity and suppress sympathetic activity in rat [80]. Since decreased parasympathetic and increased sympathetic activity were found in our study, we might assume that the effects of anesthesia were overridden by the HRV modulation provoked by DOX.…”
Section: Discussionmentioning
confidence: 60%